Penerapan Metode Weighted Product dan Rank Order Centroid dalam Sistem Pendukung Keputusan Pemilihan Pupuk Padi - Lut Faizal; Miftah Fadhli As'ad; Irfan Irfan (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2026)
Choosing the right type of fertilizer is a crucial factor in increasing rice productivity. Problems often faced by farmers are a lack of understanding of the nutritional content of fertilizers and limited access to credible agricultural information. To overcome these challenges, this research aims to develop a Decision Support System (SPK) based on the Weighted Product (WP) and Rank Order Centroid (ROC) methods to help farmers choose the best fertilizer. The ROC method is used to determine the weight of criteria based on priority ranking, while the WP method is used to evaluate and rank fertilizer alternatives based on predetermined weight values. The criteria used in this study include nitrogen, phosphorus, potassium, sulfur, organic content, price, and availability in the local market. The fertilizer alternatives analyzed are: Urea, SP-36, ZA, NPK Phonska, KCL and Petroganik. The test results show that NPK Phonska is the best fertilizer alternative, followed by ZA and Urea.